Meningkatkan Peran Ekonomi Kreatif Potensial (Cake Pisang “IMPIAN”) Menjadi Produk Oleh-Oleh Khas Andalan Masyarakat Tuban. - Hariyanti Hariyanti; Rokhadi Rokhadi; Dede Mariyani (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
The more creative students there are in a country, the more poverty and unemployment can be minimized. This is in accordance with the statement by Mark G. Hanna and Buddy Robinson, 1994 that there are three main strategies for empowerment in the practice of social change, namely traditional, direct action, and transformation. 1) Traditional strategy, suggests knowing and choosing the best interests freely in various circumstances, 2) Direct-action strategy, requiring the dominance of interests that are respected by all parties involved, viewed from the perspective of changes that may occur, and 3) Transformative strategy, shows that long-term mass education is needed before identification of self-interest. The creation of students who are broad-minded and have the ability to develop businesses can grow the Indonesian economy.